2017
DOI: 10.15208/beh.2017.11
|View full text |Cite
|
Sign up to set email alerts
|

Ownership structure and performance of professional service firms in a declining industry: Evidence from Vietnamese securities firms

Abstract: This study posits that the declining industry is a good institutional environment to examine the relationship between ownership structure and firm performance of Vietnamese securities firms. This downturn decreases the return on investment of the industry and creates incentives for managers to expropriate shareholders more severely. In addition, different groups of shareholders recognizing the status of the industry may have their own reactions which are likely to affect firm performance. Using pooled OLS regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 46 publications
4
12
2
Order By: Relevance
“…The larger the size in terms of total assets, the more productively efficient the firms are. This finding supports other works on the correlation between larger size, lower unit costs and greater economies of scale such as Weber (1999, 2008), Johnston and Madura (2000), Demirbag et al (2016), Lee, Kim and Kang (2014), Nguyen et al (2017); Hu and Fang (2010), Liao (2018). However, it is against the finding of Goldberg et al (1991) that small companies had economies, while large and diverse companies had diseconomies of scale.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The larger the size in terms of total assets, the more productively efficient the firms are. This finding supports other works on the correlation between larger size, lower unit costs and greater economies of scale such as Weber (1999, 2008), Johnston and Madura (2000), Demirbag et al (2016), Lee, Kim and Kang (2014), Nguyen et al (2017); Hu and Fang (2010), Liao (2018). However, it is against the finding of Goldberg et al (1991) that small companies had economies, while large and diverse companies had diseconomies of scale.…”
Section: Resultssupporting
confidence: 90%
“…Fourth, the firms which have foreign ownership have a less efficient performance than domestic institutional shareholder ownership. This finding is contrary to the studies of Demirbag et al (2016), Nguyen et al (2017) and Bayyurt and Akin (2014), however, it supports the findings of Phung and Mishra (2016) in their study on foreign ownership and listed firms' performance in Vietnam. They found that the performance of listed firms decreased when the level of foreign ownership was higher than 43 per cent.…”
Section: Resultscontrasting
confidence: 69%
See 3 more Smart Citations